2000
DOI: 10.2214/ajr.175.4.1751047
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of Breast Cancer with II-Gauge Vacuum Suction Biopsy

Abstract: The cancer underestimation rate with vacuum suction biopsy was 9.5%. The underestimation rate for calcifications (16.3%) was significantly higher than that for masses (1.6%) (p = 0.007). The percentage of the lesion removed was an important factor in reducing underestimation, as reflected by the percentage of calcifications retrieved and the instances of complete resolution of the lesion seen on mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
3
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 18 publications
4
60
3
7
Order By: Relevance
“…So underestimation rate using US-guided CNB could be not related with clinical condition. Some reports show that almost underestimated breast cancers (93%) with vacuum suction biopsy were reported as calcifications on mammogram (Philpotts et al, 2000). Our study suggest that the underestimation rate for calcifications were 9.4% (7/74) on mammogram and 12.5% (5/40) on US imaging, although we could not have targeted calcification only lesion on US imaging.…”
Section: Resultscontrasting
confidence: 55%
“…So underestimation rate using US-guided CNB could be not related with clinical condition. Some reports show that almost underestimated breast cancers (93%) with vacuum suction biopsy were reported as calcifications on mammogram (Philpotts et al, 2000). Our study suggest that the underestimation rate for calcifications were 9.4% (7/74) on mammogram and 12.5% (5/40) on US imaging, although we could not have targeted calcification only lesion on US imaging.…”
Section: Resultscontrasting
confidence: 55%
“…Technical advances in percutaneous core needle biopsy, such as increasing needle diameter from 14-gauge to 11-gauge and adding a vacuum device, have allowed larger samples of tissue to be obtained (5,6), substantially improving the accuracy of diagnosis. Despite these improvements, the rate of underestimation for ADH has been reported as 10% to 26% for 11-gauge vacuum-assisted biopsy (VAB) (2,14,(21)(22)(23)(24)(25)(26)(27)(28). In this study, 11-gauge SVAB was associated with a lower rate of underestimation for ADH (20.6%), compared to USguided 14-gauge automated biopsy (41.7%) (P = 0.007).…”
Section: Discussionmentioning
confidence: 84%
“…They also found that the risk of underestimation did not increase with the maximum size of the lesion for ADH, with SVAB (24,25). Decreased underestimation rates with SVAB were found to be statistically significant if the maximum diameter of the lesion was less than 10 mm (2).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations